Sintering aid mixture, solid ion conductor, and method for producing solid ion conductor

JP7638818B2Active Publication Date: 2025-03-04SCHOTT AG
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021125423
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-07-31
Filing Date
2021-07-30
Publication Date
2025-03-04
Estimated Expiration
2041-07-30

Smart Images

  • Figure 0007638818000001
    Figure 0007638818000001
  • Figure 0007638818000002
    Figure 0007638818000002
  • Figure 0007638818000003
    Figure 0007638818000003
Patent Text Reader

Abstract

To provide a sintering aid mixture for sintering a solid ion conductor for a solid-state battery, an electrode material, or the like.SOLUTION: A sintering aid mixture includes at least one sol-gel precursor and / or at least one sol-gel precursor produced from at least one sol-gel precursor.SELECTED DRAWING: Figure 1a
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a sintering aid mixture for sintering solid ion conductors, electrode materials, or the like for solid state batteries.

[0002] The present invention further relates to a solid ionic conductor.

[0003] The present invention further relates to a method for producing a solid ion conductor, electrode material, or the like for a solid-state battery.

[0004] The present invention also relates to the use of a sintering aid mixture for reducing the sintering temperature during sintering of a solid ion conductor, electrode material or the like for a solid-state battery.

[0005] Although generally applicable to any solid state battery, the present invention will be described with respect to lithium solid state batteries. [Background technology]

[0006] Lithium solid-state batteries are based on the conduction of charge carriers in the form of lithium ions using a solid electrolyte, said lithium ions being provided, for example, by oxide-based ceramic materials, such as lithium-lanthanum-zirconium oxide (LLZO) or lithium-aluminum-titanium phosphate (LATP).

[0007] It is known that in the manufacture of said lithium solid-state batteries, oxide-based ceramic materials are prepared in the form of powders, which are then subsequently pressed, slip-cast or sheet-cast or by other ceramic forming processes into porous preforms (green bodies) of the subsequent battery components, such as separator membranes, cathodes or the like. At the interfaces between adjacent particles in said green bodies of powders, migration resistances arise during the ion conduction of the battery components thus manufactured, which reduces their overall electrical conductivity.

[0008] It is further known to sinter the preforms of the battery components produced by the ceramic molding process in order to reduce the resulting migration resistance or interface resistance and thus also to increase the overall electrical conductivity of the battery components. The corresponding sintering process requires temperatures above about 850° C., especially when the green body contains ceramic materials. In addition, sintering additives can be added to produce dense sintered bodies or generally to control the properties of the sintering process.

[0009] Furthermore, in the manufacture of cathodes for lithium solid-state batteries, materials such as nickel-manganese-cobalt oxide or lithium-manganese-cobalt oxide or electronic conductors based on carbon compounds, such as conductive carbon black, graphite or the like, are also used, which are, however, temperature-sensitive and are damaged by the sintering temperatures above about 850° C.

[0010] An additional problem is that at high sintering temperatures, evaporation of lithium-containing compounds can occur, which also reduces the electrical conductivity of the battery components, an effect that is exacerbated when lithium-free sintering additives are utilized.

[0011] Known oxide-based sintering additives, such as those made of inorganic lithium salts, can indeed reduce the temperature required for the sintering process, but not enough to avoid damage to the battery components. Oxide-based sintering aids of this type are known, for example, from US 2011 / 0177397 A1. Further sintering aids are known, for example, from Korean Patent Publication No. 2017-0034581 A or Chinese Patent Publication No. 109037759 A.

[0012] Furthermore, it is known to use sintering additives with low melting points, such as fluorides, to reduce the sintering temperature. However, these have the disadvantage that most are not oxide-based. Furthermore, known sintering aids are often easily volatile and, upon decomposition, undesirable gases can be formed. Similarly, the sintering process is then less controllable. [Prior art documents] [Patent documents]

[0013] [Patent Document 1] US Patent Application Publication No. 2011 / 0177397 [Patent Document 2] Korean Patent Publication No. 2017-0034581 [Patent Document 3] China Patent Application Publication No. 109037759 [Patent Document 4] German Patent No. 102014100684 Summary of the Invention [Problem to be solved by the invention]

[0014] It is therefore an object of the present invention to provide a sintering aid mixture, a solid ion conductor and a method for producing a solid ion conductor, which provides the lower temperatures required for the sintering process of lithium-based materials, in particular below 1100° C., particularly preferably below 850° C., and at the same time provides battery components with high electrical conductivity. It is a further object of the present invention to provide an alternative sintering aid mixture, an alternative solid ion conductor and an alternative method for producing a solid ion conductor.

[0015] In one embodiment, the present invention solves the above problem by a sintering aid mixture comprising at least one sol-gel precursor and / or at least one sol-gel precursor prepared from at least one sol-gel precursor for sintering solid ion conductors, electrode materials or the like for solid-state batteries.

[0016] In a further embodiment, the present invention solves the above problem by a solid ion conductor, in particular a lithium ion conductor, which comprises a sintering aid mixture according to any one of claims 1 to 6.

[0017] In a further embodiment, the present invention solves the above problem by a method for producing a solid ion conductor, electrode material or the like for a solid-state battery, comprising a sintering process using a sintering aid mixture according to any one of claims 1 to 6.

[0018] In a further embodiment, the present invention solves the above-mentioned problem by the use of a sintering aid mixture according to any one of claims 1 to 6 for reducing the sintering temperature during sintering of solid ion conductors, electrode materials or the like for solid-state batteries to a temperature which is reduced by at least 20° C., preferably by 50° C., particularly preferably by 100° C., compared to a variant not containing a sintering aid, in particular to a temperature below 1100° C., in particular below 1000° C., preferably below 900° C., in particular below 840° C., preferably below 800° C.

[0019] These temperatures are especially true for LLZO as a solid lithium ion conductor material. For LATP, a decrease to significantly lower temperatures below 700° C. can be expected.

[0020] One advantage achieved hereby is that it is possible to reduce the temperature required for the sintering process of the lithium-based material, in particular to carry this out at temperatures below 1100° C., in particular below 1000° C., preferably below 900° C., in particular below 850° C., without a substantial decrease in the electrical conductivity of the sintered battery components. A further advantage is that the sintering aid mixture can be provided simply and cost-effectively. A further advantage achieved hereby is that the sintering activity can be substantially increased with the sintering aid mixture. In particular, it is thereby possible to use lower sintering temperatures to achieve comparable densification relative to sintering without the sintering aid mixture and / or to achieve stronger densification at comparable sintering temperatures.

[0021] In particular, a further advantage of the sintering aid mixture can be that the sintering temperature that is normally used to obtain the desired densification of a sintered body when sintering the sintered body without the sintering aid mixture can be reduced by more than 50° C., in particular more than 70° C., preferably more than 100° C., in particular more than 150° C., preferably more than 200° C., in particular more than 300° C., when the sintering aid mixture is added to the sintered body. The sintered body then has the desired densification.

[0022] In other words, the present invention provides, in one embodiment, a sintering aid mixture that allows the sintering temperature normally used to obtain the desired densification of the sintered body to be reduced by more than 50° C., in particular more than 70° C., preferably more than 100° C., in particular more than 150° C., preferably more than 200° C., in particular more than 300° C., when the sintered body contains the sintering aid mixture and at the same time has the same desired densification, compared to a sintered body sintered without the sintering aid mixture.

[0023] In particular, a further advantage of the sintering aid mixture can be that the sintering temperature that is normally used to obtain the desired densification of a sintered body when sintering the sintered body without the sintering aid mixture can be reduced by more than 5%, in particular more than 7.5%, preferably more than 10%, in particular more than 12.5%, preferably more than 15%, in particular more than 20-25%, when the sintering aid mixture is added to the sintered body, and the sintered body then has the desired densification.

[0024] In other words, in one embodiment, the present invention provides a sintering aid mixture that allows a reduction in the sintering temperature typically used to obtain the desired densification of the sintered body, when the sintered body has the sintering aid mixture and at the same time has the same desired densification, of more than 5%, in particular more than 7.5%, preferably more than 10%, in particular more than 12.5%, preferably more than 15%, in particular more than 20-25%, compared to a sintered body sintered without the sintering aid mixture.

[0025] The term "sintering aid mixture" should be understood in the broadest sense and, in particular in the claims and preferably in the description, relates to one or more auxiliaries, additives and / or additives for the sintering process. In particular, the sintering aid mixture may have a single component.

[0026] The term "sol-gel" should be understood in the broadest sense and particularly in the claims and preferably in the specification relates to a sol-gel process for producing non-metallic inorganic or hybrid polymeric materials from colloidal dispersions (sols).

[0027] The term "sol-gel precursor" is to be understood in the broadest sense and in particular in the claims and preferably in the description relates to a substance or mixture of substances which is a starting material for the sol-gel process.

[0028] The term "sol-gel precursor" is to be understood in the broadest sense and in particular in the claims and preferably in the description relates to a substance or substance mixture which has been produced using said sol-gel precursor and thus to a substance or substance mixture which is subsequent in process engineering terms for the sol-gel process using said sol-gel precursor.

[0029] Further features, advantages and further embodiments of the present invention are described below or will be apparent therefrom.

[0030] According to an advantageous further development, the sol-gel precursor is in the form of a powder, so that the sintering aid mixture can be introduced in a simple manner prior to the sintering process of the solid ion conductor, electrode material or the like.

[0031] According to a further advantageous further development, the sol-gel precursor is prepared as a stoichiometric mixture of at least two sol-gel precursors. The advantage of this is the simple preparation of the sol-gel precursor.

[0032] According to a further advantageous further development, the at least one sol-gel precursor and / or the at least one sol-gel precursor produced from the at least one sol-gel precursor is lithium-containing, the advantage of which is that not only can the temperature for the subsequent sintering process be reduced by means of this, but likewise the evaporation of lithium from the battery components is reduced or prevented.

[0033] According to a further advantageous further development, the at least one sol-gel precursor is free of inorganic and / or non-oxide anions, so that, for example, the incorporation of the respective anions into the structure of the battery component and thus the decrease in the ionic conductivity of the battery component can be avoided or at least reduced.

[0034] According to a further advantageous further development, the at least one sol-gel precursor comprises at least one metal-organic compound, in particular an alcoholate, acetate or the like, preferably lithium acetate and / or nitrate. The advantage of this is that such sol-gel precursors do not contain inorganic anions that tend to intercalate into the crystal structure of the solid ion conductor that can be subsequently sintered. Thus, their functionality is prevented from being undesirably altered.

[0035] According to a further advantageous further development of the solid ion conductor, it comprises lithium-lanthanum-zirconium oxide and / or lithium-aluminum-titanium phosphate, the advantage of which is the high electrical conductivity and the simple manufacture of the solid ion conductor.

[0036] According to a further advantageous further development, the sintering aid mixture is added to the solid ion conductor in a proportion of up to 15% by weight, in particular 0.01% to 10% by weight, preferably 1% to 7.5% by weight, in particular 1% to 5% by weight, preferably 1% to 4% by weight, The advantage of this is not only that the sintering temperature can be efficiently reduced, but also that the electrical conductivity of the solid ion conductor can be significantly increased.

[0037] Advantageously, the electrical conductivity of the solid ionic conductor according to the invention is increased by at least a factor of 1.5, preferably at least a factor of 2, particularly preferably at least a factor of 3, compared to a solid ionic conductor without sintering aid, from which the advantage of the increased overall electrical conductivity of the solid ionic conductor as a result of the addition of the sintering aid mixture according to the invention becomes apparent.

[0038] According to a further advantageous further development of the method, the sintering method is carried out at a temperature below 1100° C., in particular below 1000° C., preferably below 900° C., in particular below 840° C., preferably below 800° C. Thus, the evaporation of the charge carrier material, in particular lithium ions, during the production of the solid ion conductor is effectively prevented. In other words, the decrease of the ionic conductivity of the solid ion conductor can be effectively prevented.

[0039] Further important features and advantages of the invention emerge from the dependent claims, the drawings and the accompanying description of the drawings on the basis of the drawings.

[0040] It is understood that the features mentioned above and which may be further described below can be used not only in the respective indicated combinations but also in other combinations or alone, without departing from the scope of the invention.

[0041] Preferred implementations and embodiments of the present invention are illustrated in the drawings and described in more detail in the following specification, where like reference numbers refer to the same or similar or functionally identical parts or elements. [Brief description of the drawings]

[0042] [Figure 1a] 1 is a plot of normalized area as a function of temperature for a powder pressed body according to an embodiment of the present invention; [Figure 1b] A plot of normalized area as a function of temperature for a powder pressed body according to an embodiment of the present invention; and [Diagram 2] 1 is a table of overall electrical conductivity and relative density of sintered bodies according to embodiments of the present invention.

[0043] Preparation of a reference sample without the addition of a sintering aid mixture according to an embodiment of the present invention In the following, the synthesis of the GK-LLZO and SG-LLZO materials is first described, followed by pressing them into sintered bodies and sintering the sintered bodies.

[0044] Synthesis of glass-ceramic LLZO (GK-LLZO) The synthesis of GK-LLZO was carried out by a melting method, as described, for example, in DE 10 2014 100 684 B4, which is hereby incorporated by reference. The oxides of the metal cations were melted together and homogenized in a skull crucible, which here consisted of a vertical metal tube cooled with water. The starting materials were combined in the crucible and the batch was preheated with a burner so that sufficient electrical conductivity was achieved. Further heating was carried out by irradiation with high-frequency energy by an induction coil. A layer of solidified melt was formed on the cooled metal tube, which separated the crucible wall from the liquid melt. This made it possible to prevent possible reactions between the crucible material and the melt. The batch was homogenized with a water-cooled stirrer. After the reaction was complete, the heating was switched off and the melt solidified in the crucible in the form of a massive block.

[0045] First, the agglomerated blocks are broken into smaller pieces with hammers and chisels. These are then fed into a jaw crusher in one or more passes until pieces of a maximum size of 10 mm in the longest dimension are produced. These are then crushed into pieces of a size d 99 Crushed to less than 1 mm.

[0046] 1 kg of coarsely ground GK-LLZO powder with a particle size of less than 1 mm is charged into the counter-current jet mill. Using a downstream sifter, a powder fraction is obtained, which, after further separation of the fine fraction in a cyclone, is 50 = 1.4 μm, d 90 = 2.9 μm and d 99 = 4.1 μm. The particle size is measured using the method of static light scattering according to the ISO 13320-1 standard with a particle size measuring device of the type 1064 of the company CILAS. The measurements are carried out in water as a medium and evaluated by the Fraunhofer method.

[0047] Synthesis of ceramic LLZO prepared by sol-gel route (SG-LLZO) The synthesis of SG-LLZO as a reference material for powders prepared by the glass-ceramic route was carried out by a modified sol-gel method. To this end, a zirconium oxide precursor powder (Zr-VP) was first prepared.

[0048] For the preparation of the Zr-VP, zirconium propoxide solution (70% in 1-propanol) (234.04 g, 0.5 mol, 1.0 equiv.) was charged into a round-bottom flask. Acetylacetone (50.08 g, 0.5 mol, 1.0 equiv.) was added via a dropping funnel with vigorous stirring, and the resulting yellowish solution was stirred at room temperature for 1 h after the addition was complete. The solution was added dropwise to water (23.78 g, 1.32 mol, 2.6 equiv.) with constant stirring, and stirred for another 30 min after the addition was complete. Upon the water addition, the solution turned deep orange in color and became more viscous.

[0049] The solution was quickly stripped of solvent on a rotary evaporator, yielding an orange-yellow powder, which was stored in a crystallizing dish in an oven at 125° C. for 5 hours to remove any remaining solvent.

[0050] For the preparation of SG-LLZO, lanthanum(III) acetate penthydrate (30.75 g, 0.09 mol, 1 equiv.) in approximately 130 mL of ethanol was charged into a round-bottom flask and added dropwise to 2-(2-methoxyethoxy)acetic acid, resulting in a milky cloudy solution. Zr-VP (12.68 g, 0.06 mol, 0.67 equiv. eq.) was dissolved in 60 mL of ethanol and added to the lanthanum(III) acetate solution with stirring. Lithium acetate dihydrate (23.58 g, 0.23 mol, 2.57 equiv.) and aluminum chloride hexahydrate (1.74 g, 0.007 mol, 0.08 equiv.) were added to the solution, and the orange cloudy solution was stirred at room temperature overnight. The solvent was removed using a rotary evaporator and the resulting yellowish orange powder was calcined at 1000 °C for 7 h in a ZrO2 crucible with a heating rate of 10 K / min. The resulting colorless powder was ground under a nitrogen atmosphere and pulverized using a planetary mill.

[0051] Manufacturing of sintered bodies In order to measure the electrical conductivity of GK-LLZO and SG-LLZO with and without sintering aids and to carry out lithium connection experiments, sintered bodies of various powders were produced. For this purpose, firstly, green bodies were prepared in air. About 0.3-0.5 g of the powders were transferred into a cylindrical steel press mold and firmly pressed with a steel piston. The powders were then uniaxially pressed with a defined force (30 kN) for 2 minutes and then sintered at 1200 °C.

[0052] For further experiments and measurements, the surface of the sintered body was polished with silicon carbide polishing paper in an argon glove box (MBraun, H2O <1 ppm, O2 <1 ppm). The thickness of the sintered body was about 1 mm after the polishing.

[0053] Contact of the sintered body with a gold layer For sample preparation, the sintered bodies were produced as described above and, after polishing, a thin gold layer (about 130 nm) was sputtered using a Leica device for 4 minutes and a current strength of 60 mA. The assembly of the sintered bodies into suitable measuring cells was carried out in an argon glove box.

[0054] The impedance of the sintered body was measured using a broadband dielectric spectrometer equipped with an Alpha-A High Performance Frequency Analyzer equipped with a Novocontrol cryostat. The frequency range of the measurement was 4 MHz to 10 MHz, and an AC voltage amplitude of 20 mV was applied.

[0055] The measurement data was evaluated using the software ZView 2.9 (Scribner Associates, Inc. USA).

[0056] Example for manufacturing samples with addition of sintering aid mixture according to an embodiment of the present invention Below, the example of a sol-gel precursor of lithium aluminate (LiAlO2) as a sintering aid shows how the sintering temperature required for sintering GK-LLZO and SG-LLZO is reduced, as is the dependence of the electrical conductivity on the amount of sintering aid added.

[0057] Synthesis of lithium aluminate (LiAlO2) sol-gel precursor Aluminum isopropoxide (21.20 g, 0.10 mol, 1.0 equiv.) (here used as sol-gel precursor for Al2O3) was dispersed in 67 mL of ethyl acetate and added to 40 mL of acetic acid (41 g, 0.68 mol, 6.8 equiv.) with stirring. A milky white suspension was obtained. Lithium acetate dihydrate (23.58 g, 0.23 mol, 2.57 equiv.) (here used as sol-gel precursor for Li2O) was dissolved in 57 mL of ethanol and added to the suspension with stirring. Stirring was continued for 1 h at room temperature. The suspension was evaporated and the gel was dried at 100 °C for about 20 h. The resulting colorless powder was finely ground. A colorless powder was obtained as lithium aluminate (LiAlO2) sol-gel precursor.

[0058] Lithium aluminate (LiAlO2) sol-gel precursor as a sintering aid mixture To investigate the effect of sintering additives or sintering aid mixtures, a sol-gel precursor of lithium aluminate (LiAlO2) was prepared by the sol-gel route and combined with GK-LLZO and SG-LLZO in a proportion of 15 wt.% each. The powder mixtures were subsequently pressed into pellets, sintered and electrochemically investigated similarly to the reference samples.

[0059] Characterization of samples according to embodiments of the invention (i.e., produced with the addition of a sintering aid mixture) (and in comparison a reference sample produced without the addition of a sintering additive) For a first phenomenological characterization of the sintering behavior, the LiAlO2 sol-gel precursor and the mixture of GK-LLZO and LiAlO2 sol-gel precursors and the mixture of SG-LLZO and LiAlO2 sol-gel precursors, respectively, were examined in a heating microscope (see FIG. 1). In detail, FIG. 1a shows a plot of the normalized area of ​​the powder pressed bodies of LiAlO2 sol-gel precursor (reference number 102), GK-LLZO (reference number 101) and GK-LLZO + 15 wt.% LiAlO2 sol-gel precursor (reference number 103) versus temperature, and FIG. 1b shows a plot of the normalized area of ​​the powder pressed bodies of LiAlO2 sol-gel precursor (reference number 202), SG-LLZO (reference number 201) and SG-LLZO + 15 wt.% LiAlO2 sol-gel precursor (reference number 203) versus temperature. The thermocouples present in the measuring device were only able to reliably measure temperatures above 350° C., so the diagrams in FIGS. 1a and 1b start from this temperature.

[0060] For the LiAlO2 sol-gel precursor 102, 202, the shrinkage starts slowly at about 810° C. and becomes more intense from a temperature of 900° C. until there is a linear drop in the normalized area to 85% of the original area. From 1020° C., the shrinkage is reduced to about 82% by the end of the measurement (1200° C.).

[0061] From the comparison of the heating microscope (EHM) curves of GK-LLZO 101 and GK-LLZO+15 wt.% LiAlO2 sol-gel precursor 103, the advantageous effect of the sintering aid mixture LiAlO2 sol-gel precursor 102 on the reduction of the normalized sample area can be fully recognized. From about 550° C., a first very slight shrinkage occurs, which is only noticeable at 700° C. in the case of GK-LLZO 101. In the further course 101, from 950° C., a more significant decrease in the area starts, and from a temperature of 1050° C., the curve changes to a very steep course, so that the sample area shrinks by almost 30% (1150° C.). The densification increases further, but less significantly, with increasing temperature to about 65% of the normalized sample area. For the mixture of SG-LLZO and LiAlO2 sol-gel precursor (15 wt%) 103, clear differences also occur in the EHM compared to the pure LLZO powder 102. Here, the shrinkage starts easily already at 880°C, and the curve 103 changes to a steeper course from about 1050°C until the minimum normalized area is reached in the course of the curve (about 82%).

[0062] Therefore, based on the EHM data, the action of the LiAlO2 sol-gel precursor 102 as a sintering aid mixture is clear: for both powders GK-LLZO and SG-LLZO, sintering already occurs at lower temperatures and the densification of the samples is clearly greater.

[0063] In addition to the phenomenological EHM investigation, LiAlO2 was also combined with GK-LLZO and SG-LLZO (two mixtures each with 5 wt.% of LiAlO2 sol-gel precursor) and sintered. The action of the LiAlO2 sol-gel precursor as a sintering additive could be confirmed exclusively by visual inspection. The produced sintered bodies appear more homogeneous and more stable overall. In addition to the relative density of the sintered bodies, Figure 2 also lists the electrical conductivity of the pure LLZO variants, i.e. GK-LLZO and SG-LLZO, and the LLZO-LiAlO2 mixtures each with 5 wt.% of LiAlO2 sol-gel precursor.

[0064] Already with the smaller addition of 5 wt. % LiAlO2 sol-gel precursor as sintering aid mixture, better electrical conductivity was obtained in both cases than in the pure LLZO variant (see FIG. 2).

[0065] By electrochemical characterization of the sintered bodies with additionally added sintering additive (LiAlO2 sol-gel precursor) and subsequent phase analysis using powder diffraction methods, it was possible to determine that the electrical conductivity can be or is advantageously influenced by the addition of the sintering aid mixture according to the invention as sintering additive.

[0066] In summary, at least one of the embodiments of the present invention may provide at least one of the following advantages and / or features: - Simple to manufacture sintering aid - Reduction of sintering temperature by adding the sintering aid - Low-cost sintering aid - prevention of said decrease in electrical conductivity, especially in the case of lithium-based materials - Simpler manufacturing of solid-state batteries.

[0067] The invention will be described on the basis of preferred embodiments, but it is not limited thereto and can be modified in various ways. [Explanation of symbols]

[0068] 102 Plot for LA-sol-gel precursor, 101 Plot for GK-LLZO, 103 Plot for GK-LLZO + LA-sol-gel precursor, 202 Plot for LA-sol-gel precursor, 201 Plot for SG-LLZO, 203 Plot for SG-LLZO + LA-sol-gel precursor

Claims

1. A sintering aid mixture for sintering a lithium ion conductor for a solid-state battery, comprising: The sintering aid mixture is composed of a sol-gel precursor produced by a sol-gel process from at least one sol-gel precursor, and the at least one sol-gel precursor is an alcoholate or acetate and / or nitrate of aluminum and lithium.

2. The sintering aid mixture of claim 1 , wherein the sol-gel precursor is present in the form of a powder.

3. 3. The sintering aid mixture of claim 2, wherein the sol-gel precursor is prepared as a stoichiometric mixture of the two sol-gel precursors.

4. A sintering aid mixture according to any one of claims 1 to 3, wherein the acetate is lithium acetate.

5. A lithium ion conductor comprising a sintering aid mixture according to any one of claims 1 to 4.

6. 6. The lithium ion conductor of claim 5 comprising lithium-lanthanum-zirconium oxide and / or lithium-aluminum-titanium phosphate.

7. 7. The lithium ion conductor according to claim 5, wherein the sintering aid mixture is added to the lithium ion conductor in a proportion of at most 15% by weight.

8. 5. A method for producing a lithium ion conductor for a solid-state battery, comprising a sintering process using a sintering aid mixture according to any one of claims 1 to 4.

9. 9. The process according to claim 8, wherein the sintering process is carried out at a temperature which is reduced by at least 20° C. compared to a variant without sintering aids.

10. 5. Use of the sintering aid mixture according to any one of claims 1 to 4 for reducing the sintering temperature to below 1100°C when sintering lithium ion conductors for solid-state batteries.

Citation Information

Patent Citations

  • Sintering method for preparing dense garnet-type lithium ion solid electrolyte

    CN109037759A

  • Lithium manganate positive electrode material precursor, lithium manganate positive electrode material and preparation methods thereof

    CN111233042A

  • Ion-conducting glass ceramic with garnet-like crystal structure, method for producing and using such a glass ceramic

    DE102014100684A1

  • KR2017-0034581

  • All solid state battery

    US20110177397A1